General dynamical density functional theory for classical fluids - Goddard,BD; Nold,A; Savva,N; Pavliotis,GA; Kalliadasis,S (PHYSICAL REVIEW LETTERS, 2012)
We study the dynamics of a colloidal fluid including inertia and hydrodynamic interactions, two effects which strongly influence the nonequilibrium properties of the system. We derive a general dynamical density functional theory which shows very good agreement with full Langevin dynamics. In suitable limits, we recover existing dynamical density functional theories and a Navier-Stokes-like equation with additional nonlocal terms.